Pentafluoropropionamide-doped CsPbI3 film, preparation method and solar cell
The pentafluoropropionamide-doped CsPbI3 film addresses the vulnerability of CsPbI3 to water vapor by enhancing hydrophobicity and crystallinity, improving the performance and stability of perovskite solar cells.
Patent Information
- Application Number
- CN202411284372.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-07
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-20
AI Technical Summary
The black phase CsPbI3 is susceptible to invasion by water vapor at room temperature, leading to degradation and loss of effectiveness, and is prone to defects on the surface or grain boundaries, limiting the performance of perovskite solar cells.
A method is developed to prepare a pentafluoropropionamide-doped CsPbI3 film by dissolving CsI and DMAPbI3 in DMF, adding pentafluoropropionamide, and spin-coating the mixture on a substrate followed by annealing, which enhances the hydrophobicity and crystallinity of the film.
The doped CsPbI3 film exhibits improved hydrophobicity and reduced defects, resulting in enhanced photoelectric conversion efficiency and stability of perovskite solar cells, maintaining 81% of initial efficiency after exposure to a 40% humidity environment for 500 hours.
Smart Images

Figure CN119173114A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of perovskite solar cells, and in particular relates to a pentafluoropropionamide-doped CsPbI3 film, a preparation method and a solar cell. Background Art
[0002] Among all-inorganic perovskite materials, the black phase CsPbI3 has the smallest band gap (~1.7 eV), which is a necessary condition for achieving high-efficiency solar cells according to the Shockley-Queisser limit theory. However, the uncoordinated lead ions (Pb 2+ ) defects and iodine vacancies (V I ) Defect-induced non-radiative recombination is the main limiting factor for improving the photoelectric conversion efficiency of all-inorganic perovskite solar cells. On the other hand, the black phase CsPbI3 easily transforms into a yellow phase after being invaded by water vapor at room temperature and cannot continue to be used as a light-absorbing layer. Moreover, the degradation of CsPbI3 tends to occur on the surface or grain boundaries with more defects.
[0003] Therefore, increasing CsPbI3 grain size, reducing defects, and improving moisture resistance are of great significance for the preparation of high-performance perovskite solar cells (PSCs). Summary of the invention
[0004] The technical problem to be solved by the present invention is that the black phase CsPbI3 is easily invaded by water vapor at room temperature and becomes ineffective. The present application provides a pentafluoropropionamide-doped CsPbI3 film, a preparation method and a solar cell, which can improve the hydrophobicity of the CsPbI3 film.
[0005] In order to solve the above technical problems, the present invention provides a technical solution: a method for preparing a pentafluoropropionamide-doped CsPbI3 film, comprising the following steps:
[0006] Step 1, dissolving CsI and dimethylammonium lead iodide (DMAPbI3) in DMF and stirring at room temperature to obtain solution A;
[0007] Step 2, adding pentafluoropropionamide to solution A and stirring at room temperature to obtain solution B;
[0008] Step three, spin coating solution B on the substrate to prepare a film, and annealing treatment to obtain pentafluoropropionamide-doped CsPbI3 thin film.
[0009] Among them, the mass volume ratio of CsI, DMAPbI3 and DMF in step 1 is (162-195) mg:443.8 mg:(0.8-1.2) ml.
[0010] Among them, the mass volume ratio of CsI, DMAPbI3 and DMF in step 1 is 182 mg:443.8 mg:(0.8-1.2) ml.
[0011] Wherein, in step 1, stirring is performed at room temperature at a speed of 400-600 rpm / min.
[0012] The mass volume ratio of pentafluoropropionamide added in step 2 to DMF in step 1 is greater than 0 and less than or equal to 3 mg:1 ml.
[0013] The mass volume ratio of pentafluoropropionamide added in step 2 to DMF in step 1 is 2 mg:1 ml.
[0014] Wherein, the stirring at room temperature in step 2 includes: sealed stirring at room temperature; the stirring speed is 400-600 rpm / min, and the stirring time is 6-8h.
[0015] Among them, after the stirring in step 2 is completed, the perovskite precursor solution should be placed in a nitrogen glove box for standby use.
[0016] The substrate includes ITO glass, and a SnO2 film is formed on the ITO glass substrate; the solution B is spin-coated on the substrate to prepare a film, including: spin-coating the solution B on the SnO2 film to form a film.
[0017] The spin coating temperature is room temperature, the spin coating speed is 2000-3000 rpm / min, the spin coating time is 25-35 s, and the spin coating acceleration is 800-1200 rpm / min.
[0018] The annealing temperature in step 3 is 170-180° C., the annealing time is 8-13 min, and the annealing atmosphere is an inert gas.
[0019] The present application also includes a second technical method, a pentafluoropropionamide-doped CsPbI3 thin film, which is prepared by the above-mentioned method for preparing the pentafluoropropionamide-doped CsPbI3 thin film material.
[0020] The present application also includes a third technical method, a perovskite battery, comprising the above-mentioned pentafluoropropionamide-doped CsPbI3 film.
[0021] Beneficial effects of the present invention:
[0022] (1) The preparation method of pentafluoropropionamide (PFPA)-doped CsPbI3 thin film of the present application has cheap and easy-to-obtain raw materials, no need for expensive instruments and equipment, and low cost; the reaction cycle is short, the synthesis process is simple and low-cost, there is no pollution to the environment, and the thermal budget is low. The obtained CsPbI3 thin film material doped with pentafluoropropionamide (PFPA) is an all-inorganic perovskite film, which can improve the crystallinity of the all-inorganic perovskite film, reduce defects, and improve hydrophobicity. The prepared pentafluoropropionamide (PFPA)-doped CsPbI3 thin film, pentafluoropropionamide (PFPA) can form a significant passivation effect on the CsPbI3 perovskite film, mainly because the PFPA dispersed at the grain boundaries and surface of the perovskite film can form a significant passivation effect on CsPbI3. On the one hand, the C=O in pentafluoropropionamide (PFPA) can passivate the uncoordinated Pb in the perovskite film CsPbI3. 2+ On the other hand, -NH2 in pentafluoropropionamide (PFPA) can react with I in CsPbI3 - Hydrogen bond formation inhibits I - The migration of iodine vacancy defects is reduced. In addition, the CF exposed to the outside in the PFPA molecules covering the surface of the perovskite film has good hydrophobicity. The prepared pentafluoropropionamide (PFPA) doped CsPbI3 film can be used as a light-absorbing layer of titanium ore solar cells to improve the photoelectric conversion efficiency of perovskite solar cells and the stability of the device.
[0023] (2) The embodiment of the present invention adopts spin coating and annealing process to prepare pentafluoropropionamide (PFPA) doped CsPbI3 thin film material. Pentafluoropropionamide (PFPA) can form a significant passivation effect on CsPbI3 perovskite film. In the all-inorganic perovskite, the uncoordinated lead ions (Pb 2+ ) defects and iodine vacancies (V I )Defect-induced non-radiative recombination is the main limiting factor for improving the photoelectric conversion efficiency in all-inorganic perovskite solar cells.
[0024] (3) The pentafluoropropionamide (PFPA) doped CsPbI3 thin film material of the present invention is applied to a perovskite cell device, and the perovskite cell device can obtain a photoelectric conversion efficiency of 15.30%, and can maintain about 81% of the initial efficiency after being placed in a 40% humidity environment for 500 hours. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a process flow chart of the CsPbI3 thin film doped with pentafluoropropionamide (PFPA) prepared in Example 1 of the present invention.
[0026] Figure 2This is a mechanism diagram of using pentafluoropropionamide (PFPA) to dope CsPbI3 thin film material in Example 1 of the present invention.
[0027] Figure 3a This is a water contact angle diagram of the CsPbI3 thin film material of comparative example 1.
[0028] Figure 3b This is a water contact angle diagram of the pentafluoropropionamide-doped CsPbI3 thin film material of Example 1 of the present invention. Figure 3c This is a water contact angle diagram of the pentafluoropropionamide-doped CsPbI3 thin film material of Example 2 of the present invention. Figure 3d This is a water contact angle diagram of the pentafluoropropionamide-doped CsPbI3 thin film material of Example 3 of the present invention. Figure 4 These are structural characterization diagrams of the CsPbI3 thin film material of Example 1 and the CsPbI3 thin film material doped with pentafluoropropionamide of Examples 1 to 3 of the present invention, (a) X-ray diffraction spectrum, (b) (220) crystal plane diffraction peak magnification diagram, (c) (220) diffraction peak intensity diagram, and (d) (220) diffraction peak half-width diagram.
[0029] Figure 5a This is a scanning electron microscope image of the surface of the CsPbI3 thin film material of Comparative Example 1.
[0030] Figure 5b This is a scanning electron microscope image of the CsPbI3 thin film material doped with pentafluoropropionamide in Example 1.
[0031] Figure 5c This is a scanning electron microscope image of the CsPbI3 thin film material doped with pentafluoropropionamide of Example 2. Figure 5d This is a scanning electron microscope image of the CsPbI3 thin film material doped with pentafluoropropionamide of Example 3.
[0032] Figure 6 The CsPbI3 thin film material of comparative example 1 and the CsPbI3 thin film material doped with pentafluoropropionamide of examples 1 to 3 of the present invention show (a) ultraviolet-visible absorption spectrum (UV-vis), (b) Tauc spectrum, (c) photoluminescence (PL) spectrum, and (d) time-resolved photoluminescence (TRPL) spectrum.
[0033] Figure 7 It is a structural diagram of a perovskite solar cell device according to an embodiment of the present invention.
[0034] Figure 8 It is a JV diagram of a solar cell device prepared from the CsPbI3 thin film material of Comparative Example 1 and the CsPbI3 thin film material doped with pentafluoropropionamide of Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a pentafluoropropionamide (PFPA)-doped CsPbI3 thin film material. Figure 1 The process flow chart of the preparation method of the pentafluoropropionamide (PFPA) doped CsPbI3 thin film material of this embodiment is shown, which includes the following steps:
[0036] Step 1, dissolving CsI and DMAPbI3 in DMF and stirring at room temperature to obtain solution A;
[0037] Step 2, adding pentafluoropropionamide to solution A and stirring at room temperature to obtain solution B;
[0038] Step 3, spin coating solution B on a substrate to prepare a film, and placing it on a heating table at a certain temperature for annealing to obtain a pentafluoropropionamide (PFPA)-doped CsPbI3 thin film material;
[0039] The embodiment of the present invention adopts doping to prepare CsPbI3 thin film materials with improved crystallinity, reduced defects, and improved hydrophobicity. The raw materials of the present invention are cheap and easy to obtain, no expensive instruments and equipment are required, the synthesis process is simple and low in cost, the reaction cycle is short, and it is pollution-free to the environment and has a low thermal budget. The embodiment of the present invention controls the content of pentafluoropropionamide, so that the prepared pentafluoropropionamide (PFPA) doped CsPbI3 thin film material has improved crystallinity, reduced defects, and enhanced hydrophobicity, and the photoelectric conversion efficiency of the perovskite solar cell using it as the light absorption layer and the stability of the device are significantly improved.
[0040] like Figure 2 As shown in the figure, the CsPbI3 thin film material doped with pentafluoropropionamide (PFPA) prepared in the embodiment of the present invention can form a significant passivation effect on CsPbI3 by dispersing the PFPA at the grain boundary and surface of the perovskite film. The embodiment of the present invention uses a spin coating device and a thermal annealing device to prepare a CsPbI3 thin film material doped with pentafluoropropionamide (PFPA). In the all-inorganic perovskite, the uncoordinated lead ions (Pb 2+ ) defects and iodine vacancies (V I ) Defect-induced non-radiative recombination is the main limiting factor for improving the photoelectric conversion efficiency of all-inorganic perovskite solar cells. PFPA dispersed at the grain boundaries and surfaces of perovskite films can form a significant passivation effect on CsPbI3. On the one hand, C=O can passivate the uncoordinated Pb in the perovskite film. 2+ On the other hand, -NH2 can react with I - Hydrogen bond formation inhibits I -The migration of iodine vacancy defects is reduced, thereby reducing the formation of iodine vacancy defects. In addition, the CF exposed to the outside in the PFPA molecules covering the surface of the perovskite film has good hydrophobicity. Therefore, we speculate that the PFPA covering the surface of the perovskite film can also improve the hydrophobicity of the perovskite film, and ultimately enhance the stability of the battery device. The pentafluoropropionamide (PFPA)-doped CsPbI3 thin film material prepared in the embodiment of the present invention reduces the surface defects of the CsPbI3 film and improves the hydrophobicity by a simple doping method, providing a simple and effective idea for preparing efficient and stable perovskite solar cells.
[0041] In the embodiment of the present invention, the temperature of the annealing treatment is 170-180°C. In the embodiment of the present invention, the atmosphere of the annealing treatment is a nitrogen atmosphere. In other embodiments, it can also be other inert atmospheres. Among them, the temperature of the annealing treatment can be 170°C, 172°C, 175°C, 178°C, 179°C, 180°C, etc. The annealing time is 8-13min.
[0042] In an embodiment of the present invention, the mass volume ratio of CsI, DMAPbI3 and DMF in step one is (162-195) mg:435-445.8 mg:(0.8-1.2) ml, optionally 182 mg:443.8 mg:1 ml. The mass volume ratio of the pentafluoropropionamide added in step two to the DMF in step one is greater than 0 and less than or equal to 3 mg:1 ml, optionally 2 mg:1 ml. In an embodiment of the present invention, the content of pentafluoropropionamide added is controlled to achieve the best effect of the formed film.
[0043] In the embodiment of the present invention, in step 1, CsI and DMAPbI3 are added to DMF and stirred to completely dissolve by adding a clean magnetic bar and stirring in a sealed manner at room temperature, and the stirring speed is set to 400-600 rpm / min. In step 1, the time for adding CsI and DMAPbI3 to DMF and stirring until they are completely dissolved is 12 hours, and the embodiment of the present application does not limit the time for complete dissolution.
[0044] In the embodiment of the present invention, the method of adding pentafluoropropionamide to solution A and stirring completely in step 2 is to add a clean magnetic bar and stir in a sealed manner at room temperature, and the stirring speed is set to 600 rpm / min. The time for adding pentafluoropropionamide to solution A and stirring until complete in step 2 is 6-8 hours. The completely dissolved solution achieves the best effect of forming a CsPbI3 film.
[0045] In the embodiment of the present invention, the spin coating speed in step 3 is 2000-3000 rpm / min, the spin coating time is 25-35 s, and the spin coating acceleration is 1000 rpm / min. The embodiment of the present invention achieves the best effect of forming the CsPbI3 film by controlling the spin coating conditions.
[0046] In the embodiment of the present invention, the substrate is an ITO-SnO2 glass substrate. The substrate of the embodiment of the present invention adopts an ITO glass substrate, and an electron transport layer SnO2 is spin-coated on the glass substrate, and a CsPbI3 thin film material is doped with pentafluoropropionamide (PFPA), so that the CsPbI3 thin film material based on the ITO glass substrate can be applied to the field of perovskite solar cells.
[0047] In the embodiment of the present invention, the number of layers spin-coated in step 3 is 1. In the embodiment of the present invention, the thickness of the CsPbI3 film is 350-400 nm.
[0048] The present invention also includes a pentafluoropropionamide-doped CsPbI3 thin film, which is prepared by the above-mentioned method for preparing the pentafluoropropionamide-doped CsPbI3 thin film material.
[0049] The present application also includes a perovskite cell, comprising the above-mentioned pentafluoropropionamide-doped CsPbI3 film.
[0050] Among them, the pentafluoropropionamide-doped CsPbI3 film is used as the absorption layer, and the photoelectric conversion efficiency of the perovskite battery reaches more than 15.3%, and it can maintain about 81% of the initial efficiency after being placed in a 40% humidity environment for 500 hours.
[0051] For ease of understanding, this application provides the following specific embodiments.
[0052] Embodiment 1:
[0053] A method for preparing a CsPbI3 thin film doped with pentafluoropropionamide (PFPA) comprises the following steps:
[0054] Step 1, dissolve 183 mg CsI and 443.8 mg DMAPbI3 in 1 mL DMF and stir at room temperature to obtain solution A;
[0055] Step 2, adding 1 mg of pentafluoropropionamide to solution A and stirring at room temperature to obtain solution B;
[0056] Step 3: Spin-coat solution B on a substrate to form a film, and place it on a heating table at 175°C for annealing to obtain a CsPbI3 thin film material doped with pentafluoropropionamide (PFPA). The thin film is used as a light-absorbing layer to prepare a solar cell.
[0057] Embodiment 2:
[0058] The difference between this embodiment and embodiment 1 is that the amount of pentafluoropropionamide in step 1 is changed to 2 mg, and the rest is the same as embodiment 1, specifically as follows:
[0059] A method for preparing a CsPbI3 thin film doped with pentafluoropropionamide (PFPA) comprises the following steps:
[0060] Step 1, 183 mg CsI and 443.8 mg DMAPbI3 were dissolved in 1 mL DMF and stirred at room temperature to obtain solution A;
[0061] Step 2, adding 2 mg of pentafluoropropionamide to solution A and stirring at room temperature to obtain solution B;
[0062] Step three, spin-coating solution B on the substrate to prepare a film, and placing it on a heating table at 175° C. for annealing to obtain a CsPbI 3 thin film material doped with pentafluoropropionamide (PFPA).
[0063] Embodiment 3:
[0064] The difference between this embodiment and embodiment 1 is that the amount of pentafluoropropionamide in step 1 is changed to 3 mg, and the rest is the same as embodiment 1, specifically as follows:
[0065] A method for preparing a CsPbI3 thin film doped with pentafluoropropionamide (PFPA) comprises the following steps:
[0066] Step 1, dissolve 183 mg CsI and 443.8 mg DMAPbI3 in 1 mL DMF and stir at room temperature to obtain solution A;
[0067] Step 2, adding 3 mg of pentafluoropropionamide to solution A and stirring at room temperature to obtain solution B;
[0068] Step three, spin-coating solution B on the substrate to prepare a film, and placing it on a heating table at 175° C. for annealing to obtain a CsPbI 3 thin film material doped with pentafluoropropionamide (PFPA).
[0069] Example 4
[0070] A method for preparing a CsPbI3 thin film doped with pentafluoropropionamide (PFPA) comprises the following steps:
[0071] Step 1, 162 mg CsI and 435 mg DMAPbI3 were dissolved in 0.8 mL DMF and stirred at room temperature to obtain solution A;
[0072] Step 2, add 1 mg of pentafluoropropionamide to solution A, and stir the mixture under sealed condition at room temperature at a stirring speed of 400 rpm / min for 6 h to obtain solution B;
[0073] Step 3: Spin solution B onto the SnO2 film on the ITO substrate to prepare a film, the spin coating speed is 2000rpm / min, the spin coating time is 25s, and the spin coating acceleration is 800rpm / min; and put it on a 170℃ heating table and anneal it in a nitrogen atmosphere for 8min to obtain a CsPbI3 thin film material doped with pentafluoropropionamide (PFPA). And use it as a light absorbing layer to prepare a solar cell. Among them, the SnO2 film is an electron transport layer.
[0074] Example 5
[0075] A method for preparing a CsPbI3 thin film doped with pentafluoropropionamide (PFPA) comprises the following steps:
[0076] Step 1, dissolve 180 mg CsI and 440 mg DMAPbI3 in 1.2 mL DMF and stir at room temperature to obtain solution A;
[0077] Step 2, add 1.2 mg of pentafluoropropionamide to solution A, and stir the mixture under sealed condition at room temperature at a stirring speed of 500 rpm / min for 7 h to obtain solution B;
[0078] Step 3: Spin solution B onto the SnO2 film on the ITO substrate to prepare a film, the spin coating speed is 2500rpm / min, the spin coating time is 30s, and the spin coating acceleration is 1200rpm / min; and put it on a 175℃ heating table and anneal it in a nitrogen atmosphere for 10min to obtain a CsPbI3 thin film material doped with pentafluoropropionamide (PFPA). And use it as a light absorbing layer to prepare a solar cell. Among them, the SnO2 film is an electron transport layer.
[0079] Example 6
[0080] A method for preparing a CsPbI3 thin film doped with pentafluoropropionamide (PFPA) comprises the following steps:
[0081] Step 1, dissolve 195 mg CsI and 445 mg DMAPbI3 in 1.2 mL DMF and stir at room temperature to obtain solution A;
[0082] Step 2, add 1.2 mg of pentafluoropropionamide to solution A, and stir the mixture under sealed condition at room temperature at a stirring speed of 800 rpm / min for 8 h to obtain solution B;
[0083] Step 3: Spin solution B onto the SnO2 film on the ITO substrate to prepare a film, the spin coating speed is 3000rpm / min, the spin coating time is 35s, and the spin coating acceleration is 1000rpm / min; and put it on a 180℃ heating table and anneal it in a nitrogen atmosphere for 13min to obtain a CsPbI3 thin film material doped with pentafluoropropionamide (PFPA). And use it as a light absorbing layer to prepare a solar cell. Among them, the SnO2 film is an electron transport layer.
[0084] Comparative Example 1
[0085] The difference from Example 1 is that step 2 is not included, which is as follows:
[0086] 183 mg CsI and 443.8 mg DMAPbI3 were dissolved in 1 mL DMF and stirred at room temperature to obtain solution A;
[0087] Solution A was spin-coated on a substrate to form a film, and then placed on a 175°C heating table for annealing to obtain a CsPbI3 thin film material, which was then used as a light-absorbing layer to prepare a solar cell.
[0088] Experimental test:
[0089] The surface contact angle of the pentafluoropropionamide-doped CsPbI3 films of Comparative Example 1 and Examples 1 to 3 was tested. Figure 3a-Figure 3b As shown, compared with the contact angle of 58.5° of the CsPbI3 film in Comparative Example 1, the contact angles when the PFPA addition concentrations were 1 mg / mL, 2 mg / mL, and 3 mg / mL were 63.2°, 70.4°, and 76.9°, respectively. As the concentration of the PFPA additive increased, the contact angle of the CsPbI3 perovskite film gradually increased, indicating that the hydrophobicity of the perovskite film was enhanced. This is because the CF groups of the PFPA molecules distributed on the perovskite surface enhance the hydrophobicity of the perovskite surface.
[0090] like Figure 4 As shown in (a), the CsPbI3 films with different PFPA additive concentrations all have two main diffraction peaks at 14.4° and 28.8°, corresponding to the (110) and (220) crystal planes of the CsPbI3 perovskite. In addition, no other diffraction peaks appear and the characteristic peaks of the (110) and (220) crystal planes do not move, indicating that the introduction of PFPA does not change the crystal structure of CsPbI3. Figure 4(b) is the XRD spectrum of the (220) crystal plane diffraction peak, and the peak intensity and half-width of the (220) crystal plane diffraction peak are further analyzed. Figure (c) is the peak intensity diagram of the (220) crystal plane diffraction peak of Example 1-3 and Comparative Example 1, and Figure (d) is the half-width change of the (220) crystal plane diffraction peak of Example 1-3 and Comparative Example 1. Based on the change in the intensity of the (220) crystal plane diffraction peak of the perovskite film prepared with different PFPA addition concentrations, as the concentration of the PFPA additive increases, the diffraction peak intensity of the (220) crystal plane shows a trend of first increasing and then decreasing. On the contrary, the half-width of the (220) crystal plane first decreases and then increases. The changes in the intensity and half-width of the (220) crystal plane diffraction peak indicate that the introduction of the PFPA additive can effectively enhance the crystallinity of CsPbI3. When the PFPA concentration is 2 mg / mL, the (220) crystal plane diffraction peak intensity is the largest and the half-height width is the smallest, indicating that the crystallinity of the CsPbI3 film is the highest. When the PFPA concentration increases further, the decrease in the diffraction peak intensity and the increase in the half-height width indicate that the crystallinity of the perovskite film is destroyed.
[0091] like Figure 5a-5b As shown, in order to explore the effect of the introduction of PFPA additives on the surface morphology of CsPbI3 film, the surface morphology of CsPbI3 perovskite film was characterized using scanning electron microscopy (SEM). 5a is a scanning electron microscope image of the CsPbI3 perovskite film of Comparative Example 1, 5b is a scanning electron microscope image of the pentafluoropropionamide-doped CsPbI3 perovskite film of Example 1, 5c is a scanning electron microscope image of the pentafluoropropionamide-doped CsPbI3 perovskite film of Example 2, and 5d is a scanning electron microscope image of the pentafluoropropionamide-doped CsPbI3 perovskite film of Example 3. With the introduction of PFPA additives and with the increase in the concentration of PFPA additives, the originally rough surface of the CsPbI3 film gradually becomes smooth, and the grain boundaries and holes gradually decrease, indicating that the introduction of PFPA can effectively improve the surface morphology of the CsPbI3 perovskite film.
[0092] like Figure 6As shown in Figure (a), the absorbance of the film is characterized by UV-visible absorption spectroscopy. The absorbance of the perovskite film at 450-500nm is enhanced to a certain extent with the introduction of PFPA, and reaches a maximum when the added concentration is 2 mg / mL. This is due to the improvement of the quality of the perovskite film, which enhances the absorbance of the film. The Tauc curve of the perovskite film obtained by further calculation is shown in Figure (b). The introduction of the PFPA additive does not change the band gap width (1.67 eV) of the perovskite film. It shows that PFPA does not affect the perovskite lattice, but stays at the grain boundaries and surfaces of the perovskite film to produce effects. In order to further explore the effect of PFPA additives on the optoelectronic properties of perovskite films, photoluminescence tests (PL) were performed on perovskite films with different PFPA addition concentrations. The test results are shown in Figure (c), and time-resolved photoluminescence tests (TRPL) were performed. The test results are shown in Figure (d). With the increase of PFPA addition concentration, the photoluminescence (PL) intensity of the perovskite film showed a trend of first increasing and then decreasing, and reached a maximum value at 2 mg / mL, indicating that the non-radiative recombination of the perovskite film was effectively suppressed.
[0093] like Figure 7 As shown in the figure, the solar cell device structure includes, from top to bottom, a silver electrode 1, a molybdenum oxide layer 2, a Spiro-OMeTAD hole transport layer 3, a phenylethylammonium iodide (PEAI) passivation layer 4, a CsPbI3 perovskite film layer 5, a lithium fluoride (LiF) layer 6, a tin dioxide electron transport layer 7, and an ITO conductive glass 8. The pentafluoropropionamide (PFPA)-doped CsPbI3 films of Examples 1 to 3 and the CsPbI3 film of Comparative Example 1 were made into solar cell devices and subjected to IV tests. The results are shown in FIG. Figure 8 As shown, the highest efficiency JV curves of the solar cell devices of Examples 1-3 and Comparative Example 1 are compared, and the detailed parameters are shown in Table 1. The research results show that with the introduction of PFPA additives, the short-circuit current density (J SC ), open circuit voltage (V OC ), fill factor (FF), and photoelectric conversion efficiency (PCE) have all been improved. And when the addition concentration is 2 mg / mL, it reaches the maximum value, and the corresponding open circuit voltage (V OC ) is 1.10V, short-circuit current density (J SC ) is 18.95 mA / cm 2 , the fill factor (FF) is 0.73, and a photoelectric conversion efficiency (PCE) of 15.30% is obtained. The improvement in the photoelectric conversion efficiency (PCE) mainly comes from the short-circuit current density (J SC) and fill factor (FF). This is because the introduction of PFPA additives enhances the crystallinity of the perovskite film, increases the grain size of the perovskite film, and improves the surface morphology of the perovskite film, thereby enhancing the short-circuit current density and fill factor of the battery device.
[0094] Table 1 Maximum efficiency parameters of solar cell devices of Examples 1-3 and Comparative Example 1.
[0095]
[0096] In combination with the present invention, the embodiments of the present invention all obtain crystalline CsPbI3. Compared with the comparative example 1, the CsPbI3 thin film of pentafluoropropionamide of embodiments 1-3 has larger grains, fewer defects, stronger hydrophobicity, and a short-circuit current density (J SC ), open circuit voltage (V SC ), fill factor (FF), and photoelectric conversion efficiency (PCE) have all been improved. Among them, the CsPbI3 film doped with 2mg pentafluoropropionamide has larger grains, fewer defects, and stronger hydrophobicity than the undoped and doped films. When doped with 2mg pentafluoropropionamide, the short-circuit current density (J SC ), open circuit voltage (V SC ), fill factor (FF), and photoelectric conversion efficiency (PCE) have all been improved to the best.
[0097] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, any modification, substitution, or improvement made on the basis of the above description and within the method and principle of the present invention should be included in the protection scope of the present invention. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A method for preparing a pentafluoropropionamide-doped CsPbI3 thin film, characterized in that: The following steps are involved: Step 1, dissolving CsI and DMAPbI3 in DMF and stirring at room temperature to obtain solution A; Step 2, adding pentafluoropropionamide to solution A and stirring at room temperature to obtain solution B; Step three, spin coating solution B on the substrate to prepare a film, and annealing treatment to obtain pentafluoropropionamide-doped CsPbI3 thin film.
2. The method for preparing a pentafluoropropionamide-doped CsPbI3 thin film according to claim 1, characterized in that: The mass volume ratio of CsI, DMAPbI3 and DMF in step 1 is (162-195) mg: (435-445)mg:(0.8-1.2)ml.
3. The method for preparing a pentafluoropropionamide-doped CsPbI3 thin film according to claim 1, characterized in that: The mass volume ratio of pentafluoropropionamide added in step 2 to DMF in step 1 is greater than 0 and less than or equal to 3 mg:1 ml, and can be 2 mg:1 ml.
4. The method for preparing a pentafluoropropionamide-doped CsPbI3 thin film according to any one of claims 1 to 3, characterized in that: The stirring at room temperature in step 2 comprises: sealing and stirring at room temperature; The stirring speed is 400-600 rpm / min, and the stirring time is 6-8h.
5. The method for preparing a pentafluoropropionamide (PFPA)-doped CsPbI3 thin film according to any one of claims 1 to 3, characterized in that: The substrate comprises ITO glass, and a SnO2 thin film is formed on the ITO glass substrate. The step of spin coating the solution B on the substrate to form a film comprises: spin coating the solution B on the SnO2 thin film to form a film.
6. The method for preparing a pentafluoropropionamide-doped CsPbI3 thin film as claimed in claim 5, characterized in that: The spin coating temperature is room temperature, the spin coating speed is 2000-3000 rpm / min, the spin coating time is 25-35s, and the spin coating acceleration is 800-1200 rpm / min.
7. The method for preparing a pentafluoropropionamide-doped CsPbI3 thin film as claimed in claim 1, characterized in that: The annealing temperature in step 3 is 170-180° C., the annealing time is 8-13 min, and the annealing atmosphere is an inert gas.
8. A pentafluoropropionamide-doped CsPbI3 film, characterized in that: The material is prepared by the method for preparing pentafluoropropionamide-doped CsPbI3 thin film material according to any one of claims 1 to 7.
9. A perovskite battery, characterized in that: Including the pentafluoropropionamide-doped CsPbI3 film as described in claim 8.
10. A perovskite battery, characterized in that: The pentafluoropropionamide-doped CsPbI3 film is used as an absorption layer, and the photoelectric conversion efficiency of the perovskite cell reaches more than 15.3%, and after being placed in a 40% humidity environment for 500 hours, it can maintain about 81% of the initial efficiency.
